Exploring vulnerability in the criminal justice system in England and Wales - Farrugia, Laura (Routledge, 2025)
Providing a comparative analysis of both vulnerable witnesses and vulnerable suspects, this book discusses the increasingly difficult issue faced by many in modern policing, forensic psychology, criminology, and social justice studies